Assessing the Relationship among Six Sigma, Absorptive Capacity and Innovation Performance - Yusr, Maha Mohammed; Othman, Abdul Rahim; Mohd Mokhtar, Sany Sanuri (Elsevier Ltd., 2012)
Nowadays in the hypercompetitive marketplace companies try to adopt and apply many strategic approaches and initiatives that have proved its success to improve the competitive advantage, innovative abilities, and business performance in general. Thus, this study attempts to figure out the relationship between Six Sigma and innovation performance, and examine the mediating role of AC in this relationship. A questionnaire was used to collect the data from the manufacturing companies in Malaysia and Partial Least Square (PLS) was adopted to analyze the data obtained. Based on the literature review, the conceptual framework of this study is introduced. The hypotheses were tested and supported through the findings.